2013
DOI: 10.1002/ppsc.201300177
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembly Route to an Iron Phthalocyanine/Reduced Graphene Oxide Hybrid Electrocatalyst Affording an Ultrafast Oxygen Reduction Reaction

Abstract: Graphene oxide (GO) is an attractive freestanding support that can be decorated with ultrathin organic layers for facile and low‐cost fabrication of novel devices with controllable functional properties and microstructures. Here, it is reported that a hybrid material consisting of an ultrathin iron phthalocyanine (FePc) layer self‐assembled on reduced graphene oxide (rGO) exhibits excellent catalytic activity that is superior to that of commercial Pt/C for an oxygen reduction reaction (ORR). During solution pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…The OCV was 0.7-0.8 V, indicating that the PcFe/rGO acted as an excellent electrode for oxygen reduction reaction. 24 Consequently, we successfully fabricated a GOFC with a noble metal-free oxygen electrode. However, the current was small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OCV was 0.7-0.8 V, indicating that the PcFe/rGO acted as an excellent electrode for oxygen reduction reaction. 24 Consequently, we successfully fabricated a GOFC with a noble metal-free oxygen electrode. However, the current was small.…”
Section: Resultsmentioning
confidence: 99%
“…The ink was cast onto the GO paper surfaces, and then reduced by irradiating it with a 500 W Hg lamp (USH-500D, Ushio) for 10 min in order to increase the electrode conduction by reducing the GO to rGO in the electrode. 23,24 Fuel cell performance tests.-The GOFC was placed in the fuel cell test chamber ( Figure S4) at 23-25…”
mentioning
confidence: 99%
“…The peak location of 710 eV indicates the Fe 2+ state of the central iron in FePc. 29 On the other hand, the 2p 3/2 peak for FePc/GO sample seems to be asymmetric in shape and its foot extended to the higher binding energy, suggesting the presence of Fe 3+ state (713 eV 16 ) in the sample. It may be explained as follows; FePc is considered to adsorb at the oxygen site of GO preferably via coulombic interaction (Fig.…”
Section: Computational Calculationmentioning
confidence: 99%
“…Then, the electrode was subjected to the electrochemical reduction treatment in 0.1 M Na 2 SO 4 solution by applying a constant potential of ¹1.1 V for 5 min in order to remove the oxygen moieties on GO. 16 Thus obtained FePc/ER-GO/GC electrode was further pretreated by applying potential cycling between ¹0.8 and 0.2 V for 10 times in deaerated 0.1 M KOH before use. XPS analysis of the ER-GO/GC sample revealed that the relative concentration of phenolic, alcohol and ether groups (286.6 eV) was 16% and that of carbonyl and quinone groups (287.3 eV) was 2%, which suggests that a small amount of oxygen groups still remained after electrochemical reduction.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
See 1 more Smart Citation